Pengaruh Lingkungan Kerja, Budaya Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai di Dinas Pemadam Kebakaran Kabupaten Labuhanbatu Utara - Helvin Ruida Hasi; Sjahril Effendy; Muis Fauzi Rambe (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The research method uses an associative method and a quantitative descriptive approach with the help of the SPSS version 21 program where variables are measured by a Likert scale.The study population numbered 34 people, given the small number of population above, the researchers used the entire population to be the sample, where this research is called census research while the sampling technique used is saturated sampling technique, with a total sample of 34 people who are employees in the Department. North Labuhanbatu District Fire Department.While the data analysis technique used is the classical assumption test, multiple regression, t test, and F test and the coefficient of determination. The results showed a partial test that the Work Environment variable has a significant effect on employee performance, Work Culture has a significant effect on employee performance, and Work Motivation has a significant effect on employee performance at the Fire Service Office of North Labuhanbatu Regency, and simultaneously tests that the Work Environment, Culture variables Work, and work motivation have a significant effect on the performance of employees in the Fire Service of North Labuhanbatu Regency.